Error mapping of rotary tables in 4-axis measuring devices using a ball plate artifact. Issue 1 (2018) - Wang, Qichang; Miller, Jimmie; Von Freyberg, Axel; Steffens, Norbert; Fischer, Andreas; Goch, Gert
Abstract: Rotary tables as components of 4-axis measuring devices provide a quick rotary positioning in geometry measurements, but the non-trivial error motions need to be determined and compensated. This paper presents a new solution for the error mapping, which calibrates the rotary table, the 3-axis measuring device and the artifact (circular ball plate) simultaneously. Multi-measuring and approximation techniques are introduced to identify and quantify the error motions based on obtained point clouds. A mathematical model covers all the deviation sources, occurring at the movement of a rotary axis. Simulations and experimental results verify and validate the solution. The simple and flexible calibration setup together with the developed evaluation procedure enable a compensation of rotary table/axis deviations in a wide application field.